The Influence of Digital Money Usage and Trust in Digital System on the Ease of Life Activities of FEB UNJ Students - Nazwa Jelita Soleha; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study explores the impact of Digital Currency (X1) and Trust in Digital Systems (X2) on the Ease of Activities (Y) and overall convenience (Z) among FEB UNJ students. Using a quantitative survey with 155 respondents, the findings show that students perceive digital money as practical, fast, and efficient for campus transactions, while trust in digital systems enhances security and reliability. Both variables positively influence the ease of campus activities, improving productivity and overall student convenience. These results support the Technology Acceptance Model (TAM) and UTAUT, emphasizing the role of perceived usefulness and trust in promoting digital adoption. The study suggests that secure and user-friendly digital platforms are essential for enhancing academic and daily campus life.